Climate change and human activities reduced the burial efficiency of nitrogen and phosphorus in sediment from Dianchi Lake, China. (20th November 2020) - Chen, Qiuying; Ni, Zhaokui; Wang, Shengrui; Guo, Ying; Liu, Siru
Abstract: Sediments burial is a key way to reduce the mobilization of nutrients and the risk of water quality decline. Climate change and human activities are important factors affecting the burial capacity of nitrogen and phosphorus in sediments, but the role of influence factors and the driving mechanisms are unclear. Here we investigated the historical changes of the burial efficiency (BE) of nitrogen and phosphorus in the sediment profile, and the contribution and driving mechanism of climate change and human activities to the BE of nitrogen and phosphorus in Dianchi Lake, China. The results showed that the burial capacity of nitrogen and phosphorus was decreasing from 1951 to 2013, which largely attributed to the rising air temperature (AT) and decreasing sunshine hours (SH). For distribution, the BE of total nitrogen (TN) at Caohai (CH), southern Waihai (SW) and the center of the lake (CL) decreased by 314%, 574% and 659%, and the BE of total phosphorus (TP) decreased by 31%, 17% and 15%, respectively. AT, SH and fertilizer application (FA) were dominant influence factor, with a contribution rate of 46.48%–76.4%, while TN, TP and chlorophyll a (Chla) concentrations were the secondary factor, accounted for 13.45%–31.61%. Especially the increased AT was a key driver facilitating the release of nutrients, and thus reduced the BE values. AT, TN and Chla were the representative predictors of the changes of the BE in Dianchi Lake, and showed a non-linear relationship with the BE. Our results also found that the monotonic changes in AT and BE can be used to predict the changes of the burial capacity of nitrogen and phosphorus in sediment. It is implied that the warmer climate and increasingly improved water quality will further promote the release risk of nitrogen and phosphorus in sediments. Therefore, the release risk of nitrogen and phosphorus in sediments should not only focus on the study of the water environment but also pay more attention to the risks brought by climate change and how to reduce its impact. Graphical abstract: Image 1 Highlights: The burial efficiency of TN and TP in sediments of Dianchi Lake in the past 60 years declined. Warming played a key driving role for the declined burial efficiency of TN and TP due to the promotion to sediment release. The contribution for the declined burial efficiency dominated by AT, SH and FA were higher than that dominated by TN, TP and Chla. The release risk of nitrogen and phosphorus from sediments brought by climate change should be caused concern.